Quantitative Analysis of SSEA3+ Cells from Human Umbilical Cord after Magnetic Sorting. Issue 7 (July 2019) - Leng, Zikuan; Sun, Dongming; Huang, Zihao; Tadmori, Iman; Chiang, Ning; Kethidi, Nikhit; Sabra, Ahmed; Kushida, Yoshihiro; Fu, Yu-Show; Dezawa, Mari; He, Xijing; Young, Wise
Multilineage-differentiating stress-enduring (Muse) cells are a population of pluripotent stage-specific embryonic antigen 3 (SSEA3)+ mesenchymal stem cells first described by Mari Dezawa in 2010. Although some investigators have reported SSEA3+ mesenchymal cells in umbilical cord tissues, none have quantitatively compared SSEA3+ cells isolated from Wharton's jelly (WJ) and the cord lining (CL) of human umbilical cords (HUCs). We separated WJ and the CL from HUCs, cultured mesenchymal stromal cells (MSCs) isolated from these two tissues with collagenase, and quantified the percentage of SSEA3+ cells over three passages. The first passage had 5.0% ± 4.3% and 5.3% ± 5.1% SSEA3+ cells from WJ and the CL, respectively, but the percentage of SSEA3+ cells decreased significantly ( P < 0.05) between P0 and P2 in the CL group and between P0 and P1 in the WJ group. Magnetic-activated cell sorting (MACS) markedly enriched SSEA3+ cells to 91.4% ± 3.2%. Upon culture of the sorted population, we found that the SSEA3+ percentage ranged from 62.5% to 76.0% in P2–P5 and then declined to 42.0%–54.7% between P6 and P9. At P10, the cultures contained 37.4% SSEA3+ cells. After P10, we resorted the cells and achieved 89.4% SSEA3+ cells in culture. The procedure for MACS-based enrichment of SSEA3+ cells, followed by expansion in culture and a re-enrichment step, allows the isolation of many millions of SSEA3+ cells in relatively pure culture. When cultured, the sorted SSEA3+ cells differentiated into embryoid spheres and survived 4 weeks after transplant into a contused Sprague-Dawley rat spinal cord. The transplanted SSEA3+ cells migrated into the injury area from four injection points around the contusion site and did not produce any tumors. The umbilical cord is an excellent source of fetal Muse cells, and our method allows the practical and efficient isolation and expansion of relatively pure populations of SSEA3+ Muse cells that can be matched by human leukocyte antigen for transplantation in human trials.